2016
DOI: 10.1186/s12889-016-3507-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of nursery staff and parent views of healthy eating promotion in preschool settings: an exploratory qualitative study

Abstract: BackgroundIn the UK just over a fifth of all children start school overweight or obese and overweight 2–5 year olds are at least 4 times more likely to become overweight adults. This can lead to serious future health problems. The WHO have recently highlighted the preschool years as a critical time for obesity prevention, and have recommended preschools as an ideal setting for intervention. However, existing evidence suggests that the preschool environment, including the knowledge, beliefs and practices of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…It was concluded that family friendly healthy eating strategies and activities should be developed and delivered in preschool settings in a manner that is sensitive to parents’ needs [45]. Preschool staff shared ideas and strategies for engaging parents and children.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that family friendly healthy eating strategies and activities should be developed and delivered in preschool settings in a manner that is sensitive to parents’ needs [45]. Preschool staff shared ideas and strategies for engaging parents and children.…”
Section: Methodsmentioning
confidence: 99%
“…; McSweeney et al . ). It is also useful to make teachers aware of how sedentary some children are during the kindergarten/school day, as they too can help deliver strategies to decrease sedentariness in the classroom and playground (De Decker et al .…”
Section: Introductionmentioning
confidence: 97%
“…Given that childhood obesity is increasing in many countries worldwide, there is a clear need for effective interventions that target infancy or early childhood and shift children towards a healthy weight trajectory (de Onis et al 2010). School and kindergartens are a convenient environment for interventions (Waters et al 2011), but research into strategies that aid parents in modifying their children's diet and activity levels is also necessary (Gibson et al 2012;McSweeney et al 2016). It is also useful to make teachers aware of how sedentary some children are during the kindergarten/school day, as they too can help deliver strategies to decrease sedentariness in the classroom and playground (De Decker et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The number of children who start school with obesity in the UK has risen to 9.7% [ 1 ]. There are inequalities in prevalence, with children living in the most deprived areas more likely to be overweight or obese [ 1 , 2 ]. Childhood obesity often persists into adulthood [ 3 , 4 ], and due to related health issues, children with obesity can experience consequences as older children or adults.…”
Section: Introductionmentioning
confidence: 99%